Dynamika produkcji biomasy w runie lasu grądowego Galio sylvatici-Carpinetum betuli - Jagodziński, Andrzej; Janyszek, Sławomir; Pietrusiak, Katarzyna; Rawlik, Mateusz (Leśne Prace Badawcze, 2013)
We studied seasonal changes in the understorey biomass of an oak-hornbeam forest association Galio sylvatici-Carpinetum betuli . Samples were collected weekly during the most dynamic period of herbaceous layer development (April–May 2010), and every two weeks for the remainder of the growing season (June-October). Samples were collected from 10 randomly selected localities of 0.36 m 2 within the plant community. The plants harvested were separated by species, then oven-dried and weighed. There were statistically significant differences in aboveground understorey biomass during the time between harvests. For example, the lowest plant biomass (produced in 2010 and previous years) was found on April 3rd (37.2 kg/ha), whereas the two highest were on May 1st (308.1 kg/ha) and June 12th (337.6 kg/ha). The lowest biomass of plants produced in 2010 was on April 3rd (13.0 kg/ha) and the highest was on May 1st (259.8 kg/ha). When biomass of particular herbaceous plant species were analyzed, there was no one clearly dominant species. For example, from March 20th to May 22nd the biomass of Ficaria verna was the highest at ca. 36% of the total herbaceous layer plant biomass (range: 14.5–51.0%). During the next harvesting period (June–October), there were a few dominant herbaceous plant species, e.g. Geranium robertianum , Stachys sylvatica , Impatiens parviflora , Dryopteris dilatata , Dryopteris carthusiana , Dryopteris filix-mas , and Maianthemum bifolium .